Measurement of the Radioactivity Levels for Some Food Products Imported to Iraq and Estimation of the Risk to Consumers - Muhannad Kh. Mohammed; Mohammed Sh. Naji; Nabeel H. Ameen; Huda N. Karkosh (Indian Journal of Forensic Medicine & Toxicology, 2021)
In this study, Uranium (238U), Thorium (232Th), Radium (226Ra) and Potassium (40K) activity concentrationswere measured in 34 samples of biscuit, pastry, dessert, cakes and nestles manufactured in Turkey, Ukraine,Poland, Spain, France, Russia, Turkmenistan, Iran, Jordan, Algeria, India, Morocco, Kingdom of SaudiArabia, Emirates, in addition to locally produced biscuit sample manufactured in Iraq using gamma-rayspectrometry system. The average activity concentrations were 69.09±24.89 Bq/kg for 238U, 26.75±11.13Bq/kg for 232Th, 4.86±1.16 Bq/kg for 226Ra and 178.84±58.39 Bq/kg for 40K. The effective doses arisingfrom ingestion of naturally occurring radioactive materials in the investigated food samples ranged from0.068±0.02 mSv/y for adults (age > 17 y) to 0.191±0.05 mSv/y for children (age 1–2 y), with a mean valueof 0.12 mSv/y. It was found that the estimated potential radiation doses for investigated population groupswere below the dose constraint of 0.3 mSv/y. The corresponding average radiation risk for all populationgroups (6×10-6 per year) was found to be significantly lower than that considered acceptable in the relevantInternational Atomic Energy Agency (IAEA) safety standards (10-5 per year). The results presented incurrent study confirm that the potential radiation doses and radiological hazards associated with intake ofthe natural radionuclides in the imported and locally produced food species is acceptable and well withinpermissible limits. Hence, the imported and locally produced food species investigated in this study wereconsidered safe for human consumption with respect to radiological hazards.